2012
DOI: 10.1155/2012/251584
|View full text |Cite
|
Sign up to set email alerts
|

A Brief Recap of Tips and Surgical Manoeuvres to Enhance Optimal Outcome of Surgically Placed Peritoneal Dialysis Catheters

Abstract: Background. Peritoneal dialysis (PD) is an effective option of renal replacement therapy for ESRF, offering advantages over haemodialysis. Peritoneal dialysis catheter (PDC) placement is thought to be the key to successful PD and the economic advantages are lost if a patient switches to HD in the 1st year. This paper is a brief document elaborating a recap of published literature, looking at various surgical tips and manoeuvres to enhance optimal outcome of PDC placement. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 78 publications
(88 reference statements)
0
18
0
2
Order By: Relevance
“…This usually requires another trocar to place the suture. There have been, however, reports of suture fixation preventing easy catheter removal as well as being a potential cause of internal hernia or adhesions [126]. It may also impair the natural ability of the catheter to ''float'' to the largest area of PD fluid.…”
Section: Suture Fixationmentioning
confidence: 99%
See 1 more Smart Citation
“…This usually requires another trocar to place the suture. There have been, however, reports of suture fixation preventing easy catheter removal as well as being a potential cause of internal hernia or adhesions [126]. It may also impair the natural ability of the catheter to ''float'' to the largest area of PD fluid.…”
Section: Suture Fixationmentioning
confidence: 99%
“…He showed 12 % migration rate with open and none with laparoscopic, although the dysfunction rates were 4 and 6 %, respectively [112]. In a review article by Frost et al, it was recommended that ''proper rectus sheath tunneling and placement of the deep cuff are the key to reducing catheter tip migration'' (not suture fixation) [126]. However, randomized trials comparing catheter insertion with and without suture fixation or comparing suture fixation to rectus sheath tunneling have not been performed.…”
Section: Suture Fixationmentioning
confidence: 99%
“…Although a curled tip catheter has been considered by some clinicians as more likely to remain within the pelvis, offering a better drainage than a straight tip catheter (19, 20), no clear evidence supports this common belief. In 2011, Xie et al (21) compared the clinical outcomes of coiled vs. straight-end swan neck PD catheters in a prospective randomized controlled trial of 80 patients.…”
Section: Straight Vs Coiled Pd Cathetersmentioning
confidence: 99%
“…In particular, prophylactic methods for central venous catheter-related infections, dental work and colonoscopies have been well-established (469) and economically analyzed (10, 11). However, only a few studies have reported the effect of judicious use of antibiotics in minor surgeries for dialysis patients (12). In particular, discontinuation of antibiotics in arteriovenous fistula (AVF) and tendon sheath incision surgeries has yet to be investigated.…”
Section: Introductionmentioning
confidence: 99%